'A FADED REFLECTION OF THE GRACCHI':1 ETHICS, ELOQUENCE AND THE PROBLEM OF SULPICIUS IN CICERO'S DE ORATORE. (16th March 2017) - Hodgson, Louise
Abstract : This paper is as much about a particular depiction of the tribune P. Sulpicius Rufus as it is about Cicero's De Oratore, a dialogue regularly called upon by historians to give evidence on the 90sb.c. and the characters who take part in the conversation it depicts. My main focus is literary: I will argue that, given what we know about the historical Sulpicius, Cicero's choice of Sulpicius for a prominent minor role in De Oratore drives the tragic historical framework that undercuts the optimism expressed within the dialogue by the main protagonist L. Licinius Crassus for the civic value of oratory. The Rhetorica ad Herennium illustrates a certain type of allegory with the statement 'as if one should call Drusus a "faded reflection of the Gracchi"'. In De Oratore, Drusus' friend and successor Sulpicius functions as a reflection of the Gracchi and his eloquence reinforces the problem posed by such orators as the notoriously eloquent Gaius Gracchus for any such grand claims about the civic value of oratory. By examining Cicero's use of relatively recent history, we therefore discover that De Oratore is significantly more pessimistic than it may at first seem. This pessimism, however, has important implications for historians, since expanding our understanding of De Oratore as a literary construct should encourage historians to be significantly more cautious about using the text as a historical source. As Görler points out with regard to Crassus' swansong at De or. 3.4–5, although 'a naive reader of Oratorum Romanorum Fragmenta could be left with the impression that some sentences are quite well attested', most of the fragments of Crassus' speech can actually be traced back to De Oratore. Likewise, a significant proportion of the standard elements in Sulpicius' backstory go back to De Oratore and become a great deal less convincing once we accept De Oratore as a sustained fictional account featuring people who were neither as politically 'safe' nor as intellectually united as Cicero would have them be. My secondary focus in this paper is therefore on the broader lessons to be drawn from Sulpicius' role in De Oratore . I will begin by outlining the historical context of the dialogue, which was written in the mid 50s but is set in 91, a few weeks before the natural death of Crassus, one of its two protagonists. Next, I will discuss the dialogue's literary context, specifically the Platonic allusions Cicero embeds within the text. These allusions encourage us to treat De Oratore 's historical framework carefully, if not sceptically, and I will outline the 'off notes' struck by references to the Gracchi and by the presentation of Crassus and Antonius before examining the problem Sulpicius poses for a straightforwardly optimistic reading of De Oratore . I will conclude by considering first the literary implications for De Oratore of accepting that Sulpicius is a deliberately problematic character and then the historical implications of taking a sceptical approach towards De Oratore as an historical source for our picture of Sulpicius.